(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nabilla S, Safira UM, Puspita PJ, Subositi D, Maruzy A, Artika IM. 2021. Genetic diversity analysis of Piper betle from eight accessions of Indonesia based on SRAP markers. Biodiversitas 22: 3401-3408. Leaves of betel vine (Piper betle Linn.) have been used as a traditional medicine in various regions in Indonesia. However, the genetic diversity of this plant has not been well recorded. Considering its diverse usage in traditional and folk medicine, it is essential to analyze and document the genetic diversity of Piper betle L. with the aim to collect the scientific data of betel vine genetics in Indonesia. This study aims at analyzing the population structure and genetic diversity of betel vine from the Singkil, Gayo Serbajadi, Baduy, Bandung, Hutan, Kalisusu, Kaledupa, and Mekongga accession groups of Indonesia using the sequence-related-amplified polymorphism (SRAP) marker technique. Genomic DNA was isolated from each accession and then used as a template for DNA amplification using PCR. As many as 16 SRAP primer combinations were screened for the genetic diversity analysis. Optimization of primer combinations resulted in 7 selected combinations based on their ability to generate clear amplification patterns and polymorphic bands. These were then employed for genetic diversity analysis. The genetic distance dendrogram showed the lowest similarity coefficient was 0.62 and that the betel vine grouping pattern was not based on genotype. The Singkil population had the highest genetic diversity and the Hutan population had the lowest. The mean value of Nei’s genetic diversity index was 0.0985, while Shannon’s information index was 0.01459 and the percentage of polymorphic loci was 25.81. This study concluded that the level of betel vine diversity is low.